Sialomucin CD43 Plays a Deleterious Role in the Development of Experimental Heart Failure Induced by Pressure Overload by Modulating Cardiac Inflammation and Fibrosis - Kaur, Kuljeet; Velázquez, Francisco E.; Anastasiou, Marina; Ngwenyama, Njabulo; Smolgovsky, Sasha; Aronovitz, Mark; Alcaide, Pilar (Frontiers in Physiology, 2021)
Sialomucin CD43 is a transmembrane protein differentially expressed in leukocytes that include innate and adaptive immune cells. Among a variety of cellular processes, CD43 participates in T cell adhesion to vascular endothelial cells and contributes to the progression of experimental autoimmunity. Sequential infiltration of myeloid cells and T cells in the heart is a hallmark of cardiac inflammation and heart failure (HF). Here we report that CD43-/- mice have improved survival to HF induced by transverse aortic constriction (TAC). This enhanced survival is associated with improved systolic function, decreased cardiac fibrosis, and significantly reduced T cell cardiac infiltration in response to TAC compared to control WT mice. Lack of CD43 did not alter the number of myeloid cells in the heart, but resulted in decreased cardiac CXCL10 expression, a chemoattractant for T cells, and in a monocyte shift to anti-inflammatory macrophages in vitro. Collectively, these findings unveil a novel role for CD43 in adverse cardiac remodeling in pressure overload induced HF through modulation of cardiac T cell inflammation.